A Decision Support System To Determine The Best Natural Feed For Fish Cultivation Using Topsis Method - Abdul Malik; Ester Frescila Simbolon; Lukman; Tiara Adinda (Journal of Intelligent Decision Support System (IDSS), 2022)
Natural feed in the cultivation of carp (Cyprinus carpio) is a very important effort to do so that the cultured fish can breed quickly and of course in good health. Sometimes carp cultivators are confused about deciding which natural feed is good. This study aims to select the best natural carp feed using a Decision Support System (DSS) with the TOPSIS method. This method uses an alternative approach to the ideal solution called preference value. In this study using several criteria, namely C1: Protein; C2 : Fat; C3 : Carbohydrates; C4 : Feed Prices; C5: Yes. From the calculations performed using the TOPSIS method, the highest preference level with a value of 1 is A1. The results of the Decision Making System with the TOPSIS method from natural selection of carp that can be used by farmers, namely earthworms.